Analysis of substrate specificity of the PaeR7 endonuclease: effect of base methylation on the kinetics of cleavage. - Ghosh, S S (1990)
In murine cells expressing the PaeR7 endonuclease and methylase genes, the recognition sites (CTCGAG) of these enzymes can be methylated at the adenine residue by the PaeR7 methylase and at the internal cytosine by the mouse DNA methyltransferase. Using nonadecameric duplex deoxyoligonucleotide substrates, the specificity of the PaeR7 endonuclease for unmethylated, hemi-methylated, and fully methylated N6-methyladenine (m6A) and C5-methylcytosine (m5C) versions of these substrates has been studied. The Km, Kcat, and Ki values for these model substrates have been measured and suggest that fully or hemi-m6A-methylated PaeR7 sites in the murine genome are completely protected. However, the reactivity of fully or hemi-m5C-methylated PaeR7 sites is depressed 2900- and 100-fold respectively, compared to unmodified PaeR7 sites. The implications of the kinetic constants of the PaeR7 endonuclease for these methylated recognition sites as they occur in murine cells expressing this endonuclease gene are discussed.